Updates in Epinephrine Guidelines (Actualité en allergologie et en immunologie au Canada, 2025)
Epinephrine is the first line treatment for anaphylaxis, which is a serious allergic reaction that can rapidly progress and may cause death. As a nonselective adrenergic agonist, epinephrine rapidly works to increase vasoconstriction and peripheral vascular resistance, increase cardiac output, reverse bronchoconstriction and mucosal edema, and inhibit the release of mediators of inflammation from mast cells and basophils. The anaphylaxis guidelines developed by the Joint Task Force on Practice Parameters (JTFPP) in 2020, the World Allergy Organization (WAO) in 2020, and the European Academy of Allergy and Clinical Immunology (EAACI) in 2021 advise clinicians to prescribe self-injectable epinephrine to individuals at risk of anaphylaxis and educate them on when and how to administer it. In 2023, the JTFPP updated its anaphylaxis practice parameter to address seven key topic areas, including multiple questions and recommendations related to epinephrine prescription and use. The practice parameter authors graded each recommendation as conditional or strong, based in part on the certainty of the supporting evidence. We provide an overview of key recommendations and discuss their applications in the Canadian context.It is important to note that in Canada, EpiPen® autoinjectors are currently the sole epinephrine delivery devices available with premeasured doses of epinephrine for the emergency treatment of allergic reactions. These autoinjectors should be administered intramuscularly into the anterolateral thigh. Additional epinephrine devices may become available in the future, including the first epinephrine nasal spray (neffy®). There is a wider variety of epinephrine devices available in the United States, including multiple brands of epinephrine autoinjectors (Adrenaclick®, Auvi-Q®, EpiPen®/EpiPen® Jr., and generic versions). Additionally, there is one brand of epinephrine prefilled syringe (Symjepi™) and one brand of nasal spray (neffy®). Although the anaphylaxis practice parameter update was published before the U.S. Food and Drug Administration had approved neffy®, we believe its recommendations for epinephrine prescription and use may be appropriately extended to include epinephrine nasal spray where it is available.